Conventional and omics approaches shed light on Halitzia cheese, a long-forgotten white-brined cheese from Cyprus - Papademas, Photis; Aspri, Maria; Mariou, M.; Dowd, Scot E.; Kazou, Maria; Tsakalidou, E. (My University, 2019)
Production and ripening of Halitzia cheese was examined by conventional physicochemical and microbiological analyses along with state-of-the art metagenomics. Cheese was made from (A) raw goat milk without the addition of starters; (B) pasteurised goat milk without the addition of starters; (C) pasteurised milk with the addition of starters. The type and counts of microorganisms were mainly influenced by ripening time; microbial counts for lactic acid bacteria were predominant and remained stable with little or no variation throughout ripening. Coliforms and coagulase positive staphylococci declined during ripening and at the end of ripening the staphylococci were not detected. Yeasts were detected at low counts but in great diversity throughout ripening. Metagenomics analysis confirmed the results obtained by the classical microbiological analysis. The physicochemical parameters during ripening were also determined; at 60 days the pH value and moisture, fat, protein, ash, and salt contents did not significantly differ amongst cheese types.
Keywords: Lactic acid; Halitzia cheese; Cyprus; Pasteurization; Lactic acid bacteria; Microbiological analysis